2017
DOI: 10.1080/02755947.2017.1280567
|View full text |Cite
|
Sign up to set email alerts
|

Nearshore Habitat and Fish Assemblages along a Gradient of Shoreline Development

Abstract: Littoral habitat is a critical component of lake ecosystems. Expansion of residential development along lakeshores has led to habitat modification, which may alter lentic fish communities. Previous studies have linked lakeshore development to reductions in abundance of aquatic vegetation and coarse woody structure (CWS), and many have quantified the influence of the density of docks on aquatic habitat structure and individual fish species. However, few studies have quantified fish assemblages relative to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…As with coarse wood, macrophytes are directly removed (Asplund andCook 1997, Radomski andGoeman 2001) via management strategies (e.g., hand-pulling, herbicide, suction and mechanical harvesting, benthic barriers) to facilitate recreational activities, particularly in front of active lakefront property (Payton and Fulton 2004). Submergent taxa were the dominant growth form and we detected emergent and floating-leaf taxa in only 5% and 17% of our sampling quadrats, as seen in previous studies (Radomski and Goeman 2001, Jennings et al 2003, Dustin and Vondracek 2017. Despite the dominance of submerged taxa, we found lower macrophyte biovolume along developed vs. forested shorelines, supporting previous observations of macrophyte cover (Merrell et al 2009).…”
Section: Effects Of Lakeshore Development Water Quality and Herbicide Use On Littoral Habitatsupporting
confidence: 90%
See 1 more Smart Citation
“…As with coarse wood, macrophytes are directly removed (Asplund andCook 1997, Radomski andGoeman 2001) via management strategies (e.g., hand-pulling, herbicide, suction and mechanical harvesting, benthic barriers) to facilitate recreational activities, particularly in front of active lakefront property (Payton and Fulton 2004). Submergent taxa were the dominant growth form and we detected emergent and floating-leaf taxa in only 5% and 17% of our sampling quadrats, as seen in previous studies (Radomski and Goeman 2001, Jennings et al 2003, Dustin and Vondracek 2017. Despite the dominance of submerged taxa, we found lower macrophyte biovolume along developed vs. forested shorelines, supporting previous observations of macrophyte cover (Merrell et al 2009).…”
Section: Effects Of Lakeshore Development Water Quality and Herbicide Use On Littoral Habitatsupporting
confidence: 90%
“…In addition to winter drawdown magnitude, lakeshore development contributed to explaining littoral habitat variability. Along lakeshore development, our observed patterns of reduced and less complex coarse wood (Christensen et al 1996, Jennings et al 2003, Francis and Schindler 2006, Merrell et al 2009), reduced sediment organic matter (Francis et al 2007), and reduced macrophyte abundance and altered macrophyte composition (Radomski and Goeman 2001, Jennings et al 2003, Merrell et al 2009, Dustin and Vondracek 2017) has been well documented. Decreases of coarse wood recruitment is a function of lake riparian deforestation and direct removal of coarse wood within a lake (Francis and Schindler 2006).…”
Section: Discussionmentioning
confidence: 70%
“…For example, increasing lakeshore development has been shown to reduce abundance of aquatic plants, macroinvertebrates, and fish in littoral areas by reducing coarse woody debris, nutrient cycling, and habitat diversity (Brauns et al . Dustin and Vondracek ). However, previous studies have shown mismatches between protected waterbodies and protected catchments.…”
mentioning
confidence: 99%
“…This can be due to 36 two reasons. First, surveys among both the general population (Meyerhoff et In light of previous work, we expected lakes managed by anglers to be heavily modified along the 48 shoreline to accommodate angling sites and access to anglers (Dustin & Vondracek, 2017 ; O'Toole et 49 al., 2009). Although we did record higher accessibility in angler-managed lakes (in particular the 50 extension of trials), at the lake-level the degree of aquatic and riparian vegetation was found to be 51 significantly larger in angler-managed systems compared to unmanaged lakes.…”
Section: Discussionmentioning
confidence: 99%